Casein hydrolysates produced via sequential enzymatic hydrolysis: characterisation and their effect on calcium uptake by Caco-2 cell line - Chew, Lye Yee; Toh, Gaik Theng; Ismail, Amin; Shafie, Nurul Husna; Mat Daud, Zulfitri 'Azuan (John Wiley and Sons, 2024)
While dietary components such as phytate reduce calcium absorption, bioactive peptides could potentially enhance calcium absorption. This study aimed to characterise the peptides derived from casein and assess their effect on calcium uptake by Caco-2 cells. Casein was subjected to hydrolysis by Alcalase and Flavourzyme to produce 4-h and 16-h casein hydrolysates. High-performance liquid chromatography analysis showed that hydrolysis caused significant increases and decreases in the content of some amino acids. Casein hydrolysates achieved 40.36% and 52.64% degree of hydrolysis, as determined by the o-phthaldialdehyde method. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis and dynamic light scattering analyses revealed that the peptides had molecular weight less than 15 kDa and diameter between 100 and 1000 nm. The 4-h casein hydrolysate enhanced calcium uptake by Caco-2 cells monolayer at low calcium intake, possibly via transcellular absorption. These results provide insight into the nutraceutical potential of casein hydrolysates as enhancer of calcium absorption.